Exploring the Strategies for Indicating Research Gaps Used by Authors in English Education Research Article Introductions - M. Affandi Arianto; Maulluddul Haq; Jufrizal Jufrizal (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2023)
The trend of topics in language education research is affected by how authors convince readers about the issues being discussed. However, the persistence of the topic is not based on the number of scholars who have conducted the research, for instance, collaborative writing topics, but it focuses more on the newness to be contributed to the advancement of knowledge by indicating research gaps. Therefore, this qualitative study, which is specified into genre analysis, aims to describe the strategies for indicating research gaps and the area of gaps that are still needed to be fulfilled in the research of collaborative writing. A corpus consisting of 20 research article introductions (RAIs) published in highly reputable journals with high-impact factors was compiled and subjected to analyze, respectively (i.e., using the frameworks of Lim, 2012 and Ewijk, 2018) the types of research gap strategies and the areas of gaps that have been focused on by the authors. The findings show that the strategy of stating the absence of a specific area in the research of collaborative writing is employed in a vast majority (45.45%). Besides, the area of impact is found as the promising area of gap (occurred 24 times) that the authors tend to focus on. The pedagogical implications of this study are also discussed in this article.